(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Vovk N. A case study of consumer culture of the future teachers of technology education. In article questions of studying of a problem of formation of consumer culture of future teachers of technological education are considered, levels and indicators of consumer culture of students are defined. The culture of consumption is a set of resistant forms of the social interaction fixed in norms and values, means of communication which are often transferred from generation to generation. It is shown in existence of rather resistant forms, consumption models.